A 10-Year Immunopersistence Study of Hepatitis E Antibodies in Rural Bangladesh. Issue 7 (23rd March 2018) - Kmush, Brittany L; Zaman, Khalequ; Yunus, Mohammed; Saha, Parimalendu; Nelson, Kenrad E; Labrique, Alain B
Abstract: Hepatitis E virus (HEV) is a major cause of acute viral hepatitis in Southeast Asia. Several studies have suggested that antibody persistence after HEV infection may be transient, possibly increasing the risk of reinfection and contributing to the frequency of outbreaks in HEV-endemic regions. The specific conditions under which antibodies to HEV are lost, or "seroreversion" occurs, are poorly understood. Here, 100 participants from population-based studies in rural Bangladesh were revisited in 2015, 10 years after a documented HEV infection, to examine long-term antibody persistence. Twenty percent (95% confidence interval: 12.0, 28.0) of the participants no longer had detectable antibodies at follow-up, suggesting that antibodies generally persist for at least a decade after infection in rural Bangladesh. Persons who were seronegative at follow-up were generally younger at infection than those who remained positive (14.4 years vs. 33.6 years; P < 0.0001). This age-dependent antibody loss could partially explain cross-sectional seroprevalence data from Southeast Asia, where children have reportedly low antibody prevalence. The results of this study provide new insight into the immunological persistence of HEV infection in a micronutrient-deficient rural population of South Asia, highlighting the importance of age at infection in the ability to produce long-lasting antibodies against HEV.